Self-Emulsifying Drug Delivery Systems: An Alternative Approach to Improve Brain Bioavailability of Poorly Water-Soluble Drugs through Intranasal Administration - Sara Meirinho; Márcio Rodrigues; Adriana O. Santos; Amílcar Falcão; Gilberto Alves (MDPI AG, 2022)
Efforts in discovering new and effective neurotherapeutics are made daily, although most fail to reach clinical trials. The main reason is their poor bioavailability, related to poor aqueous solubility, limited permeability through biological membranes, and the hepatic first-pass metabolism. Nevertheless, crossing the blood-brain barrier is the major drawback associated with brain drug delivery. To overcome it, intranasal administration has become more attractive, in some cases even surpassing the oral route. The unique anatomical features of the nasal cavity allow partial direct drug delivery to the brain, circumventing the blood-brain barrier. Systemic absorption through the nasal cavity also avoids the hepatic first-pass metabolism, increasing the systemic bioavailability of highly metabolized entities. Nevertheless, most neurotherapeutics present physicochemical characteristics that require them to be formulated in lipidic nanosystems as self-emulsifying drug delivery systems (SEDDS). These are isotropic mixtures of oils, surfactants, and co-surfactants that, after aqueous dilution, generate micro or nanoemulsions loading high concentrations of lipophilic drugs. SEDDS should overcome drug precipitation in absorption sites, increase their permeation through absorptive membranes, and enhance the stability of labile drugs against enzymatic activity. Thus, combining the advantages of SEDDS and those of the intranasal route for brain delivery, an increase in drugs' brain targeting and bioavailability could be expected. This review deeply characterizes SEDDS as a lipidic nanosystem, gathering important information regarding the mechanisms associated with the intranasal delivery of drugs loaded in SEDDS. In the end, in vivo results after SEDDS intranasal or oral administration are discussed, globally revealing their efficacy in comparison with common solutions or suspensions.